Isang bula...nawawala ([s.l. Cecile G. Alvarez], 1989)
A documentary drama on the conditions of the people and the disaster brought by flood due to improper sanitation in their environment.
Henry Duval, editor.
Cast : Chat Silayan, Ed Feist, Henry Duval.
Keywords: Environment protection -- Metro Manila